Wearing out the Watchdog: The Impact of SEC Case Backlog on the Formal Investigation Process - Bonsall, Samuel B.; Holzman, Eric R.; Miller, Brian P. (The Accounting Review, 2024)
ABSTRACT We examine a comprehensive set of investigations by the SEC’s Division of Enforcement offices to provide evidence on the consequences of these office’s busyness on the formal investigation process. We find that higher office case backlog decreases the likelihood of an investigation into a restating firm. Our results show no evidence that higher backlogs affect the SEC’s ability to pursue cases involving revenue recognition issues and high insider trading, which is consistent with the agency’s stated priorities. But our findings indicate that busy SEC offices are less likely to pursue cases with the largest shareholder losses, which is inconsistent with SEC priorities. Backlog also impacts pursued investigations, leading to more prolonged investigations, a lower Accounting and Auditing Enforcement Releases likelihood, and smaller SEC penalties. Our evidence suggests that busyness undermines the SEC’s investigation process. JEL Classifications: G18; G38; K42; M41.